2007
DOI: 10.1111/j.1440-1819.2007.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

International study on antidepressant prescription pattern at 20 teaching hospitals and major psychiatric institutions in East Asia: Analysis of 1898 cases from China, Japan, Korea, Singapore and Taiwan

Abstract: The purpose of the present study was to review the prescription patterns of antidepressants in different countries in East Asia. The survey was conducted in China, Japan, Korea, Singapore and Taiwan from October 2003 to March 2004 using the unified research protocol and questionnaire. Twenty teaching hospitals and major psychiatric hospitals participated and a total of 1898 patients receiving antidepressants were analyzed. The survey provided a number of interesting characteristics on the prescription patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 18 publications
8
37
4
Order By: Relevance
“…Depressive disorders, anxiety disorders and mixed anxiety and depressive disorders were the most common indications for antidepressant use, accounting for 40.8% of the total prescriptions. This finding is also similar to other studies conducted elsewhere [12][13][14][16][17][18]. Antidepressants were prescribed more in females than in males, a finding that is similar to what is observed in some Western countries [12][13][14].…”
Section: Discussionsupporting
confidence: 81%
“…Depressive disorders, anxiety disorders and mixed anxiety and depressive disorders were the most common indications for antidepressant use, accounting for 40.8% of the total prescriptions. This finding is also similar to other studies conducted elsewhere [12][13][14][16][17][18]. Antidepressants were prescribed more in females than in males, a finding that is similar to what is observed in some Western countries [12][13][14].…”
Section: Discussionsupporting
confidence: 81%
“…8 The finding of this study also similar with finding of other study from the West and multi-country study from East Asia. 5,11,12 However, the percentage of prescription of SSRIs in the present study is higher than that reported in these studies. In the present study Mirtazepine formed the 8% of the total antidepressant prescriptions.…”
Section: Discussioncontrasting
confidence: 56%
“…Many authors have commented on national differences in management of depression. 20,[78][79][80] In Europe and the US, 74% and 67% of those with mental illness, respectively, receive no adequate treatment. 21,24 In the European Study of Epidemiology of Mental Disorders project conducted in Belgium, France, Germany, Italy, the Netherlands and Spain, 24 6% of the sample was defined as being in need of mental health care but 48% of these participants reported no formal healthcare use.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%